Intussusception Caused by Cecal Duplication in an Adult: A Case Report - Eric Bergeron; Normand Gervais (Case Reports in Surgery)
Cecal duplication is a rare congenital malformation and majority of the cases are discovered in the first years of life. Ileocolic intussusception is also a rare situation encountered in adults. A 19-year-old female presented with acute abdominal pain and bowel occlusion in relation with an ileocecal intussusception. She underwent an emergent laparotomy and ileocecal resection. A cecal duplication cyst was found to be the cause of the intussusception. While duplications and intussusception are very rare situations encountered in the adult life, the presence of both at the same time remains frankly anecdotal. The present case demonstrates that intussusception may likely be involved with any cecal lesion, like duplication.